In-Silico evaluation of Anti-Leishmanial compounds of selected pharmacophore - Rana, Sindhuprava; Sivaperumal, R (Journal of Drug Delivery and Therapeutics, 2018)
In this study, out of sixteen compounds, only thirteen compounds have shown hydrogen bonding with the modeled cathepsin B protein of L donovani, remaining compound (C1D13416238, Posaconazole. and CID 6082033) did not show any hydrogen bonding with ligands. So, these 13 compounds which show hydrogen bonding with modeled protein could be considered as most potent lead compounds having inhibitory activity at either promastigote stage or amastigote stage of Leishmania donovani. Few compounds demonstrated better docking score to either AutoDock4.0 or GOLD v2.l but some compound did not show any hydrogen bonding with modeled protein in either docking software tool. Thus, it could be concluded that generated experimental compounds could have potential as pharmacological tool against Visceral Leishmaniasis. Keywords: Cysteine Protease, Vinyl Hydrazide, Antileishmanial Drugs, Licochalcone, Visceral Leishmaniasis.